Circadian oscillations of cytosine modification in humans contribute to epigenetic variability, aging, and complex disease - Oh, Gabriel; Koncevičius, Karolis; Ebrahimi, Sasha; Carlucci, Matthew; Groot, Daniel Erik; Nair, Akhil; Zhang, Aiping; Kriščiūnas, Algimantas; Oh, Edward S.; Labrie, Viviane; Wong, Albert H. C.; Gordevičius, Juozas; et al. (Genome Biology, 2019)
Maintenance of physiological circadian rhythm plays a crucial role in human health. Numerous studies have shown that disruption of circadian rhythm may increase risk for malignant, psychiatric, metabolic, and other diseases. Extending our recent findings of oscillating cytosine modifications (osc-modCs) in mice, in this study, we show that osc-modCs are also prevalent in human neutrophils. Osc-modCs may play a role in gene regulation, can explain parts of intra- and inter-individual epigenetic variation, and are signatures of aging. Finally, we show that osc-modCs are linked to three complex diseases and provide a new interpretation of cross-sectional epigenome-wide association studies. Our findings suggest that loss of balance between cytosine methylation and demethylation during the circadian cycle can be a potential mechanism for complex disease. Additional experiments, however, are required to investigate the possible involvement of confounding effects, such as hidden cellular heterogeneity. Circadian rhythmicity, one of the key adaptations of life forms on Earth, may contribute to frailty later in life.